The Expressive Illocutionary Acts Found in Webtoon True Beauty and Their Translation into Indonesian - Ni Wayan Pering Muliawati; I Nyoman Sedeng; Ida Ayu Made Puspani (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2020)
The research is aimed to find the expressive of illocutionary acts found in the comic and analyze the technique of translation implemented by the translator while translating comic ‘True Beauty’. The data used to support all the analysis for this study were taken from the Webtoon comic entitled ‘True Beauty’ with its translation into Indonesian ‘Secret of Angel’ of season 1. Even though the title in Indonesian is in English, but all conversation in the comic is in Indonesian. Documentation method was used in this study by reading the data source attentively and doing note-taking. This research was designed using qualitative method, and the result of analysis was descriptively explained. The theory supporting this study was proposed by Leech (1993) illocutionary speech act, theory of translation technique written by Molinda and Albir, and ethnography of SPEAKING proposed by Hymes (2009). The results of this study showed that there were 47 expressive illocutionary acts found in the comic. the expressive illocutionary act forms found were: thanking with 23 data, apologizing with 13 data, surprising with 5 data, dislike with 2 data, congratulating with 4 data. the translation technique employed by the translator were; literal translation (37), particularization (6), modulation (3), and discursive creation (1).